2019
DOI: 10.1101/711382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The most common RNF43 mutant G659Vfs41 is fully functional in inhibiting Wnt signaling and unlikely to play a role in tumorigenesis

Abstract: RNF43 is an E3 ligase that inhibits Wnt signaling by ubiquitinating Wnt receptors for degradation. It is mutated in various cancer types with the most recurrent mutation being the frameshift G659Vfs41 with frequencies of ~5-8% in colon, stomach and endometrial cancers. The mutation has always been assumed to be loss-of-function that would lead to increased Wnt signaling and tumorigenesis, yet no functional characterization has been reported. We analyzed the distribution of the G659Vfs41 mutation and its associ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…A recent study claims RNF43 G659fs is a passenger mutation, based on its effects on the Wnt pathway [29]. This is consistent with this study, where we did not find the Wnt pathway to be impacted by RNF43 G659fs by either eVIP Pathway analysis nor in our validation.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study claims RNF43 G659fs is a passenger mutation, based on its effects on the Wnt pathway [29]. This is consistent with this study, where we did not find the Wnt pathway to be impacted by RNF43 G659fs by either eVIP Pathway analysis nor in our validation.…”
Section: Discussionsupporting
confidence: 93%
“…Finding shared fs-deletions in RNA-seq and fs-peptides in MS/MS samples suggests that fs-neoantigens are present both at transcriptional and protein levels. Similar to our discovery, a few published reports identified the same shared fs-deletions and characterized their potential biological role (Giannakis et al, 2014;Tu et al, 2019). The retained expression of fs-derived neoepitopes may be due to the fact that their RNA can exhibit a high rate of turnover and processivity within cancer cells that is otherwise not deleterious.…”
Section: Discussionsupporting
confidence: 79%
“…The E3 ligase RNF43 (Ring Finger Protein 43) inhibits Wnt signaling by ubiquitinating Frizzled receptors for degradation ( Tu et al, 2019 ). Mutations in RNF43 occur in approximately 5–7% of PDAC ( Aguilera and Dawson, 2021 ) and may serve as a useful biomarker for patient selection during clinical development of Wnt inhibitors, as it was shown that RNF43 mutant PDAC cell lines and xenograft models were sensitive to the porcupine inhibitor LGK974 ( Jiang et al, 2013 ).…”
Section: Wnt Pathway Is Another Factor In Pdac Chemoresistancementioning
confidence: 99%